Mild and Efficient Oxidation of Aromatic Alcohols and Other Substrates Using NiO2/CH3COOH System - Mohammad Kooti; Mehdi Jorfi (E-Journal of Chemistry)
A variety of aromatic alcohols were efficiently oxidized to their corresponding aldehydes and ketones in good to excellent yields using nickel peroxide activated by acetic acid. Some thiols and amines were also readily oxidized by this oxidant under mild conditions.